CFD predictions of the aerodynamic characteristics of S1223 airfoil at low Reynolds’ number - Jha S.; Jayakumar G.; Abdulgafoor C.P.; Vadlamani N.R.; Ghosh S. (My University, 2025)
This research investigates the prediction of lift characteristics of the high-lift S1223 airfoil at a low Reynolds number of 2 × 105 using different numerical methods. High-lift airfoils are crucial in applications like micro aerial vehicles and small-scale wind turbines, where low Reynolds numbers are expected. Results from Reynolds Averaged Navier Stokes (RANS) simulations employing k - ω SST and Spallart-Almaras (SA) turbulence models, k- ω (γ) SST transition/turbulence model, an in-house wall-resolved Large Eddy Simulation solver, COMPSQUARE, and the open-source panel-method based Xfoil were compared with wind tunnel data from literature. While the SA and k-(γ) models accurately predict the lift characteristics for angle-of-attack, α, up to 12°, these models predict early stall and fail to capture maximum Cl. Xfoil simulations, on the other hand, predict maximum Cl accurately, but produces a lift curve that appears shifted left compared to the experiments. Comparison of surface pressure coefficients across the numerical methods indicate that Xfoil predicts lower pressure on part of the suction surface compared to the RANS and LES computations, while having very similar pressures on the pressure side. Contour plots of resolved and modeled turbulent kinetic energy from COMP-SQUARE and the RANS simulations (with the k- ω (γ) SST model) respectively show similar transition locations for α = 0° and 8°, but differ significantly at α = 14° with the COMP-SQUARE results predicting largely attached flow with transition of the boundary layer while the RANS computation shows large scale flow separation without reattachment. © 2024, American Institute of Aeronautics and Astronautics Inc, AIAA. All rights reserved.